(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article provides a comparative linguistic and cultural analysis of aphorisms formed on the basis of kinship (relativeness) lexicon in Uzbek and English languages. The study focuses on semantic, structural, and culturally loaded aspects of aphorisms containing kinship terms such as ota/father, ona/mother, aka-brother, opa-sister, qarindosh/relative and others. The research identifies similarities and differences in how both linguistic communities conceptualize family, moral values, social norms, and interpersonal relations through aphorisms. The comparative results reveal that Uzbek aphorisms demonstrate stronger collectivistic and patriarchal features, while English aphorisms tend to reflect individualistic and humanistic worldview aspects.